The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1038/sj.bdj.4814232
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the levels of knowledge and attitudes of dental hospital staff about domestic violence following attendance at an awareness raising seminar

Abstract: RESEARCH• Assesses knowledge and attitudes of a dental team about domestic violence before and after a brief training intervention.• Post-training there was improved recognition about the dental team's role in the healthcare response to domestic violence.• Brief training can improve dental staff comfort asking patients about abuse, though whether false confi dence in dealing with abused patients results needs to be established.• We suggest that brief training be complemented with in depth practical training an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
(17 reference statements)
0
21
0
Order By: Relevance
“…Similar cautions have been offered in relation to domestic violence training in a study which also warned of generating possible false confidence in staff. 17 However we found that a high proportion (78%) acknowledged their need for further training, even if they had received previous postqualification child protection training.…”
Section: Child Protection Trainingmentioning
confidence: 63%
“…Similar cautions have been offered in relation to domestic violence training in a study which also warned of generating possible false confidence in staff. 17 However we found that a high proportion (78%) acknowledged their need for further training, even if they had received previous postqualification child protection training.…”
Section: Child Protection Trainingmentioning
confidence: 63%
“…It appears that a variety of interventions, ranging in complexity, time commitment, etc., can be successful. Only one article [98] warned that brief training – providing practitioners with a little knowledge regarding how to respond to IPV victims – could actually cause false confidence, and ultimately be potentially harmful to victims. However, this possibility was not empirically examined in any article.…”
Section: Resultsmentioning
confidence: 99%
“…These factors can make recipients less receptive to engaging with the KT intervention itself and/or impede motivation or ability to initiate subsequent behaviour change. Several interventions were particularly framed as addressing such barriers, for example interventions to improve provider comfort, including self-efficacy and acceptability, with IPV or CM knowledge e.g., [98, 106, 107]. Others suggested the inclusion of specific components to address the challenges of IPV/CM subject matter such as a hotline [103] or online chat feature [107] to provide support for those participating in online training.…”
Section: Resultsmentioning
confidence: 99%
“…Warburton et al 38 reported that a brief IPV educational program improved dental hospital staff’s attitudes and knowledge about IPV. As well, an educational program for internal medicine residents was both well received and effective at improving detection of IPV victims.…”
Section: Discussionmentioning
confidence: 99%